Paysages de l’hybridité en Birmanie - François Robinne (Moussons, 2011)
Despite the composite dimensions of any social landscape, a necesserary social coherence has to be produced. At the crossroad of peoples of multiple origins producing a complex and unstable social and linguistic diversity, the Nyaung Shwe township in the Shan State of Burma is basically shaped on the concomitant evolution of the religious circumnavigation of five Buddha images around the lake Inle and of the economic cycle based on “five days one market”. The articulation of these two religious and economic spheres not only contribute to organise the moving of the peoples and of the goods ; They institute also a political supremacy over the social lansdcape to those who control–at least symbolically–their evolution. This example could be extended to other comparable social landscapes where Buddhism operate as a federative vector (like in Thibaw Township as we shall see), where plural christianism is deeply embedded in plural ethnic revendications (as it the case in Kachin and Chin States), and finally anywhere I was able to make fieldworks in Burma, in remote areas or in urban contexts as well. In all cases the problematic to keeping apart, at least at first, the usual ethnic–or interethnic–over determinant, that is to focuse the analysis on transethnic crossroads rather than on territorial and cultural limits, such a problematic would contribute to demonstrate the inclusive dynamic of a social lanscape and the interest to take hybridity as object of study.